A árvore da vida reflexões sobre o artesanato de referência cultural do território trinacional do Iguaçu - Bernal, Mac Donald Fernandes (2015)
The text is the result of a survey on remnants of cultural evocations of the Guarani culture in the tri-border region between Brazil, Paraguay and Argentina. Linked anthropology themes, sociology, philosophy and history, the text focuses on focus on some recurring images at the time of formation of the Itaipu Lake Reservoir, demonstrating the re-articulation of knowledge through the evocation of culturally significant images regionally. With the flood caused to the lake filling, the animals living in the affected region sought refuge in the trees in order to save their lives. This phenomenon, once registered, culminated in the creation of cultural reference crafts titled as "The Tree of Life", attributed to the Guarani Indians, and that served to unite references bases of fundamental beliefs and symbols of indigenous culture of this ethnic group with strong parallelism between facts and myths. In addition to the tree, the myths of the Flood, the search for Land Without Evil, among others, make up the Guarani phenomenology around the formation of the lake. Iconographic sources, written and narrated memories are used as a means of demonstrating the everyday experience of weaving the daily task of Pai-Tavytera or Kaiowa, Mbÿá and Ñandeva s Indians, all who became homeless at the time that Itaipu s International Lake was formed.